Privacy, Corrective Justice, and Incrementalism: Legal Imagination and the Recognition of a Privacy Tort in Ontario - Bennett, Thomas (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2013)
This article considers the nature of common law development as exemplified by the recent privacy case of Jones v. Tsige. The author focuses on Jones, in which the Ontario Court of Appeal recognized the novel privacy tort of “intrusion upon seclusion”. Using a detailed analysis of the case as its basis, the article explores issues which have much wider significance for the judicial development of privacy laws: the process of incremental elaboration of the law, the moral impulses at work within it, and the relevance of imagination to its operations. By drawing out these discrete issues and analyzing the role that each plays in Jones, the article offers a framework for examining such questions in future privacy cases. Moreover, this article argues that the judgment in Jones brings valuable clarity to the analysis of the process of common law development. In particular, the essay concludes that the novel privacy tort recognized in Jones is the result of a legitimate incremental development rather than an instance of undue judicial activism.